Atomic layer deposition of functional films for Li‐ion microbatteries. Issue 2 (2nd December 2013) - Nilsen, Ola; Miikkulainen, Ville; Gandrud, Knut B.; Østreng, Erik; Ruud, Amund; Fjellvåg, Helmer
<x xml:space="preserve">Abstract</x> The lithium ion battery concept is a promising energy storage system, both for larger automotive systems and smaller mobile devices. The smallest of these, the microbatteries, are commonly based on the all‐solid state concept consisting of thin layers of electroactive materials separated by a solid state electrolyte. The fact that solid state electrolytes are required puts rather severe constraints on the materials in terms of electronic and ionic conductivity, as well as lack of pinholes otherwise leading to self‐discharge. The atomic layer deposition (ALD) technology is especially suitable for realization of such microbatteries for the Li‐ion technology. ALD has an inherent nature to deposit conformal and pinhole free layers on complex geometrical shapes, an architecture most commonly adopted for microbattery designs. The current paper gives an overview of ALD‐type deposition processes of functional battery materials, including cathodes, electrolytes, and anodes with the aim of developing all‐solid‐state batteries. Deposition of Li‐containing materials by the ALD technique appears challenging and the status of current efforts is discussed.